2023
DOI: 10.1007/s11418-023-01721-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of peony root using NMR spectroscopy and impact of the preprocessing method for NMR data in multivariate analysis

Abstract: Peony root is an important herbal drug used as an antispasmodic analgesic. To evaluate peony roots with different botanical origin, producing areas, and post-harvest processing, 1 H NMR-based metabolomics analysis was employed. Five types of monoterpenoids, including albi orin (4), paeoni orin (6), and sulfonated paeoni orin (25), and six other compounds, including 1,2,3,4,6-penta-O-galloyl-β-d-glucose (18), benzoic acid (21), gallic acid (22), and sucrose (26) were detected in the extracts of peony root sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…By contrast, the data matrix used for PCA, PLS regression, and heatmap analysis was created using HPLC peak areas and ABTS/DPPH scavenging activity data of 32 crude drug samples. Both data matrices were normalized using the Z-score transformation method, as described in our previous studies [ 46 , 47 ]. SIMCA-P (Version 14.1, Umetrics, Umea, Sweden) was used for OPLS-DA, PCA, and PLS regression, whereas Origin 2021 (Version 9.8; MicroCal, LLC, Malvern, UK) was used for heatmap analysis…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, the data matrix used for PCA, PLS regression, and heatmap analysis was created using HPLC peak areas and ABTS/DPPH scavenging activity data of 32 crude drug samples. Both data matrices were normalized using the Z-score transformation method, as described in our previous studies [ 46 , 47 ]. SIMCA-P (Version 14.1, Umetrics, Umea, Sweden) was used for OPLS-DA, PCA, and PLS regression, whereas Origin 2021 (Version 9.8; MicroCal, LLC, Malvern, UK) was used for heatmap analysis…”
Section: Methodsmentioning
confidence: 99%
“…This storage also prevented discoloration of roots and facilitated production of desirable bright color in roots, traditionally believed to be of high quality. In addition, quantitative 1 H nuclear magnetic resonance (qHNMR) analysis demonstrated that sucrose content increased significantly in root after low-temperature storage for 1 month, resulting in increased ethanol extract yield [18]. Boiling treatment triggered decomposition of polygalloylglucoses and led to significantly increased contents of P19, P22, and P23, shown by monitoring gallotannin changes using LC-IT-TOF-MS. Peeling treatment resulted in decreased P13 content; additionally in the group without boiling, the P20 content also decreased.…”
Section: Development Of Brand Peony Root In Toyamaselection From Hort...mentioning
confidence: 99%